"Relabelling" of individual early retirement pension in Finland: Application and behavioural responses using Finnish register data - Ricky Kanabar; Satu Nivalainen; Noora Järnefelt (University of Essex, Institute for Social and Economic Research (ISER), 2023)
Using rich Finnish population level registers, we examine the impact of fusing a flexible early retirement pathway with a more stringent pathway, without changing eligibility conditions, so-called "relabelling", on individual application behaviour. Our findings show that among affected cohorts the likelihood of applying for (successfully claiming) disability-related early retirement declined by 1.8 (1.5) percentage points equivalent to a relative drop of approximately 37% (39%) following the reform. Individuals with below tertiary level education and stronger lifetime labour market attachment exhibit a stronger behavioural response to the reform. We find tentative evidence of programme substitution to early retirement pathways designed to keep individuals in the labour market albeit on a part time basis. Our findings suggest that social norms and lack of awareness associated with early retirement pathways can strongly influence application behaviour even when eligibility conditions remain unchanged, offering policymakers novel ways to extend working lives.
Keywords: J26; 330; Retirement; disability; pensions; Finland; regression discontinuity